Studi Tentang Filsafat, Ilmu dan Periodesasi Perkembangannya - Muhamad Agus Nurohman (Jurnal Dewantara, 2020)
Knowledge was born since the creation of the first human, namely the prophet Adam; Knowledge developed since ancient times, but is still influenced by myth and mysticism; Knowledge is growing and becoming a science, which erodes the notion of myths and mystics, in other words, science can logicalize knowledge; Science began to develop in ancient Greece which was started by Socrates along with the birth and development of philosophy in the 6th century BC; The golden age of science began with Plato, followed by his student, Aristotle; and In the period between 650-1250 AD, the period of scientific development in the West (Europe) stopped which was called the Dark Ages.